Identification of beeswax and its falsification by the method of infrared spectroscopy - Vyshniak, Volodymyr; Dimitriev, Oleg; Litvynchuk (Vorontsova), Svitlana; Dombrovskiy, Valeriy (My University, 2018)
Infrared reflection spectra from smooth surfaces of samples (paraffin, ceresin, wax, a mixture of beeswax and ceresin, a mixture of wax paraffin and ceresin, a mixture of wax and paraffin) have a similar structure. There are two clearly expressed maxima at wavelengths of 1510 and 1581 nm. The ratio Rw(1581)/Rw(1510) varies from 1.115 to 1.265. The smallest value corresponds to natural beeswax, and the maximum value is ceresin. After shredding the sample, the infrared spectral diffuse reflections did not undergo significant changes, the most intense spectral maxima did not change its position, but the redistribution of spectral lines by intensity was happened out. There were pronounced differences in the region from 1723 to 2400 nm. The coefficient  for the reflection spectra from the smooth surface was ~ 1.2, and for the reflection spectra from the crushed samples ~ 1.1. The reflection spectra in the region from 1100 to 1350 nm have a clear maximum at a wavelength of 1212.5 nm. IR reflection spectra allowed us to clarify the difference between the natural beeswax and ceresin through the ratio of reflection features at 1510 and 1581 nm: the maximal ratio corresponded to the former, while the smallest one to the latter. The different proportion of bands corresponding to CH2 and CH3 stretching vibrations suggested that hydrocarbon chains of wax molecules are longer than those of paraffin and ceresin studied. It was found that hydrocarbon contaminants in the bee wax are associated with narrowing of the C=O band at ~1736 cm-1. The detected spectral laws will enable the identification of natural beeswax and detect its counterfeit.
Keywords: віск; парафін; церезин; спектроскопія; фальсифікат; wax; paraffin; ceresin; spectroscopy; falsification; кафедра фізики та професійної безпеки